SOX Transcription Factors as Important Regulators of Neuronal and Glial Differentiation During Nervous System Development and Adult Neurogenesis - Stevanovic, Milena; Drakulic, Danijela; Lazic, Andrijana; Ninkovic, Danijela Stanisavljevic; Schwirtlich, Marija; Mojsin, Marija (Frontiers in Molecular Neuroscience, 2021)
The SOX proteins belong to the superfamily of transcription factors that display properties of both classical transcriptional factors and architectural components of chromatin. Since the cloning of the Sox/SOX genes, remarkable progress has been made in illuminating their roles as key players in the regulation of multiple developmental and physiological processes. SOX transcription factors govern diverse cellular processes during development, such as maintaining the pluripotency of stem cells, cell proliferation, cell fate decisions/germ layer formation as well as terminal cell differentiation into tissues and organs. However, their roles are not limited to development since SOX proteins influence survival, regeneration, cell death and control homeostasis in adult tissues. This review summarized current knowledge of the roles of SOX proteins in control of central nervous system development. Some SOX transcription factors suspend neural progenitors in proliferative, stem-like state and prevent their differentiation. SOX proteins function as pioneer factors that occupy silenced target genes and keep them in a poised state for activation at subsequent stages of differentiation. At appropriate stage of development, SOX members that maintain stemness are down-regulated in cells that are competent to differentiate, while other SOX members take over their functions and govern the process of differentiation. Distinct SOX members determine down-stream processes of neuronal and glial differentiation. Thus, sequentially acting SOX transcription factors orchestrate neural lineage development defining neuronal and glial phenotypes. In line with their crucial roles in the nervous system development, deregulation of specific SOX proteins activities are associated with neurodevelopmental disorders. The overview of the current knowledge about the link between SOX gene variants and neurodevelopmental disorders is presented. We outline the roles of SOX transcription factors in adult neurogenesis and brain homeostasis and discuss whether impaired adult neurogenesis, detected in neurodegenerative diseases, could be associated with deregulation of SOX protein activities. We present the current data regarding the interaction between SOX proteins and signaling pathways and microRNA that play roles in nervous system development. Finally, future research directions that will improve the knowledge of distinct and various roles of SOX transcription factors in health and diseases are presented and discussed.